2009
DOI: 10.1097/prs.0b013e3181a80576
|View full text |Cite
|
Sign up to set email alerts
|

Botox Therapy for Ischemic Digits

Abstract: Vascular function is abnormal in patients with Raynaud's phenomenon. Although its mechanism is unknown, Botox yielded a distinct improvement in perfusion and reduction in pain in patients failing conservative management. Continued research may lead to more specific and reliable treatment for Raynaud's patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(162 citation statements)
references
References 50 publications
5
153
0
1
Order By: Relevance
“…39 -40 The ability of BoNTA to inhibit sympathetic nervous input reduces vasoconstriction, which is the most likely mechanism for improvement seen in Raynaud phenomenon patients following BoNTA injection. [7][8][9][10] The increased blood flow accompanying BoNTA administration might also be considered for other vaso-occlusive disorders and might serve as an adjunct therapy to promote healing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…39 -40 The ability of BoNTA to inhibit sympathetic nervous input reduces vasoconstriction, which is the most likely mechanism for improvement seen in Raynaud phenomenon patients following BoNTA injection. [7][8][9][10] The increased blood flow accompanying BoNTA administration might also be considered for other vaso-occlusive disorders and might serve as an adjunct therapy to promote healing.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6] In addition, botulinum toxin is emerging as a treatment modality for Raynaud phenomenon. [7][8][9][10] The mechanism of action of BoNTA at the neuromuscular junction and the functional recovery of the nerve and muscle are well established [11][12][13][14][15][16][17][18] ; however, little information is available regarding toxin effects on the local vasculature. [7][8][9]19 Arteriolar diameter and blood flow is predominantly controlled by the sympathetic nervous system, which releases norepinephrine after stimulation and results in ␣-adrenergic receptor-mediated vasoconstriction.…”
mentioning
confidence: 99%
“…All but 5 patients experienced improved vascularity and relief of pain Neumeister et al (2009) 19 pts 84% reported pain reduction at rest and improvement of the perfusion and ulcerations Fregene et al (2009) 26 pts Statistically significant improvements were noted for pain score and digit transcutaneous oxygen saturation Van Beek et al (2007) 11 patients All patients reported highly significant pain reduction and 9 pts with ulcers spontaneously healed Kossintseva (2008) One patient The BT-A treated hand had reduced swelling, color change, and pain, whereas the untreated control hand remained affected Jenkins (2013) 10 pts randomized controlled study…”
Section: Studymentioning
confidence: 95%
“…Most of these studies are case series (Liu, 2006;Heckmann et al, 2002;Kossintseva et al, 2011;Iorio et al, 2012;Serri et al, 2013) , one is randomized controlled trial (Neumeister, 2010) and two case reports (Neumeister et al, 2009;Fregene et al, 2009) (Table 3). In all of these studies the patients were presented with chronic ischemic hand pain, ulceration and loss of function.…”
Section: Raynaud Syndromementioning
confidence: 96%
“…22 In one study, 23 10 of 14 patients with Raynaud phenomenon noted an average 124% improvement in digital perfusion via laser Doppler study within 30 minutes of injection of botulinum toxin adjacent to the affected artery. Use of botulinum toxin is infrequently reported in the setting of acute thrombosis, and the mechanism of Botox's rapid effects has not been fully elucidated.…”
Section: Relieving Vasospasmmentioning
confidence: 98%